2023
DOI: 10.1039/d2ta08074e
|View full text |Cite
|
Sign up to set email alerts
|

A synergistic two-step optimization design enables high capacitive energy storage in lead-free Sr0.7Bi0.2TiO3-based relaxor ferroelectric ceramics

Abstract: Dielectric ceramic capacitors are essential components in next-generation advanced pulse power systems owing to their ultrafast charging/discharging rate and high power density, nevertheless confronting the critical challenges regarding the collaborative...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 80 publications
1
16
0
Order By: Relevance
“…Above 100 °C, the P max and P r increase with temperature, which should be caused by the thermally stimulated conduction loss that is reflected in the gradually increased dielectric loss with increasing the test temperature (Figure S3, Supporting Information). [7] As shown in Figure S16c (Supporting Information) [28,[70][71][72][73][74][75] and Figure 6e , [14,28,39,69,71,[75][76][77] the frequency-and temperature-stabilities of ES properties for the optimal NN-BNT-0.2CT ceramic can be comparable to those of recently reported lead-free ceramics.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Above 100 °C, the P max and P r increase with temperature, which should be caused by the thermally stimulated conduction loss that is reflected in the gradually increased dielectric loss with increasing the test temperature (Figure S3, Supporting Information). [7] As shown in Figure S16c (Supporting Information) [28,[70][71][72][73][74][75] and Figure 6e , [14,28,39,69,71,[75][76][77] the frequency-and temperature-stabilities of ES properties for the optimal NN-BNT-0.2CT ceramic can be comparable to those of recently reported lead-free ceramics.…”
Section: Resultssupporting
confidence: 82%
“…As histogramed in Figure 7e, E b , P d , and t 0.9 of the NN‐BNT‐0.2CT ceramic in this study also precede most recently reported lead‐free ceramics. [ 14,63,66,74,75,78 ] Overall, the designed NN‐BNT‐0.2CT ceramic is promising for the application in pulse‐power systems.…”
Section: Resultsmentioning
confidence: 99%
“…From the service life of energy storage materials viewpoint, the mechanical performance such as hardness is important on a microscopic scale. 18,22,58 For x = 0.5, non-plastic deformation S1 † for references and details).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the ESP of a dielectric material can be tailored by adjusting the phase structure to reach an optimized proportion, 20 especially an optimized R-T phase structure, which represents the balance between a high W rec and high h. Designing lead-free RFEs by tailoring the nanodomain or polar nanoregion (PNR) conguration, essentially originating from a large local random eld with intensied compositional disorder, 35 is reported to be an effective route toward enhancing the ESP. [19][20][21][22]25,26,36,37 In particular, intrinsic PNRs, including the sizes, volume fraction, and dynamic response to the external electric eld, can offer a driving force for regulating reversible domain switching, generating slim P-E loops and small P r with low hysteresis, 6,38 although accompanied by the reduction in polarization. Furthermore, it is recognized that E b is a key factor affecting W rec , and band gap (E g ) engineering and microstructure optimization can generally boost E b .…”
Section: Introductionmentioning
confidence: 99%